Strategies for Implementing Character Education Curriculum to Mitigate Adolescent Delinquency at SMK Muhammadiyah Mayong - Toni Ardi Rafsanjani; M. Abdurrozaq; Fauziyah Inayati (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to identify and analyze the implementation strategy of the character education curriculum at SMK Muhammadiyah Mayong to prevent juvenile delinquency. The primary focus is to understand the effectiveness of the character education curriculum approach in shaping positive student behavior, particularly in preventing deviant actions. Theoretical framework: The theoretical framework of this study is based on principles of character education, integrating Islamic values and theories of behavior formation through habituation and learning. Literature Review: The literature review explores character education concepts grounded in religious values in vocational school contexts, the role of teachers as role models, and the effectiveness of mentoring programs in preventing juvenile delinquency. Methods: The research employs a qualitative approach with a case study design. Data collection methods include direct observation, in-depth interviews with teachers and the principal, and documentation related to the curriculum and the implementation of character education programs. Data analysis was conducted descriptively using thematic analysis techniques to identify patterns and key themes in character education strategies. Results: The findings reveal that SMK Muhammadiyah Mayong employs specific strategies in its character education curriculum, including the integration of Islamic values into learning activities, strengthening the role of teachers as role models, and special guidance programs for students at risk of delinquency. These programs include religious activities such as routine recitations, moral value studies in subjects, and fostering discipline and responsibility through extracurricular activities. Implications: The implications of this study indicate that consistently applying Islamic values in character education can be an effective preventive measure against juvenile delinquency. These findings provide practical recommendations for other Muhammadiyah schools to develop similar programs and for education policymakers to design effective curricula for shaping students’ character. Novelty: The uniqueness (novelty) of this study lies in its in-depth analysis of how Muhammadiyah values, particularly Islamic principles, are integrated into the character education curriculum within a vocational school context. This research makes a significant contribution to the character education literature by providing new perspectives on applying religious values to prevent juvenile delinquency.